2015
DOI: 10.1186/s13104-015-1677-8
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and coronary levels of CRP, MPO, sCD40L and PlGF in patients with coronary artery disease

Abstract: BackgroundBiomarkers play a pivotal role in the diagnosis and management of patients with acute coronary syndrome. This study aimed to investigate the differences in level of several biomarkers, i.e. C-reactive protein, myeloperoxidase, soluble CD40 ligand and placental growth factor, between acute coronary syndrome and chronic stable angina patients. The relationship between these biomarkers in the coronary circulation and systemic circulation was also investigated.MethodsA total of 79 patients were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Based on these observations, it has been suggested that there is local vascular production in addition to systemic production. Interestingly, several other studies investigating trans-lesional gradients did not reproduce an increase of CRP across the culprit lesion and disputed the finding of local vascular production [9][10][11]. Our study, in which a trans-lesional CRP gradient could not be shown, corroborates with these findings.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Based on these observations, it has been suggested that there is local vascular production in addition to systemic production. Interestingly, several other studies investigating trans-lesional gradients did not reproduce an increase of CRP across the culprit lesion and disputed the finding of local vascular production [9][10][11]. Our study, in which a trans-lesional CRP gradient could not be shown, corroborates with these findings.…”
Section: Discussionsupporting
confidence: 81%
“…Appreciating that CRP binds to injured cells and activates inflammation, an evident role for CRP was suggested in the aftermath of MI [7]. Several studies focused on coronary CRP levels, varying from trans-lesional assessments (proximal and distal to the culprit lesion) [8][9][10][11][12] to studies on transcardiac gradients, i.e. from the aorta to the coronary sinus (CS) [12][13][14][15][16][17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Devaraj and Jialal demonstrated a pivotal activity of CRP in polarizing human monocyte differentiation toward a proinflammatory M1 macrophage phenotype (via NF κ b and by binding to the Fc- γ receptors CD32 and CD64) and inhibiting M2 macrophages [36]. The pathophysiological relevance of intraplaque CRP was further supported by its positive association with clinical instability of CAD patients [18, 37]. Considering the heterogeneity of atherosclerotic plaques, the main novelty of our study was the demonstration that intraplaque CRP levels can differentially be associated with plaque vulnerability parameters, depending on where the plaque is positioned.…”
Section: Discussionmentioning
confidence: 99%
“…6 Fong et al in their study concluded that MPO levels in systemic circulation directly reflects those in coronary circulation and is a potential marker in predicting coronary artery diseases. 7 Hence, predominance of evidence supports an association between MPO level and CAD and dose-response relationship between MPO level and CAD severity. 8 Cardiac troponin levels are very sensitive and specific for myocardial damage regardless of underlying cause.…”
mentioning
confidence: 99%